ANALISIS KESENJANGAN PENGUKURAN ASET BIOLOGIS ANTARA KEPMENDESAA 136/2022 DAN PSAK 241 PADA BADAN USAHA MILIK DESA: PERBANDINGAN HISTORICAL COST DAN FAIR VALUE MEASUREMENT - Difi Aqilla Febiansyah; Muhamad Rafy Khairu; Rosmaria Anggelina Simanjuntak; Zaza Dhina Tri Pamungkas (Jurnal Akuntansi Kompetif, 2026)
Abstract: This study aims to analyze the normative gap between Kepmendesaa 136/2022 (SAK ETAP historical cost approach) and PSAK 241 (fair value biological assets approach) and its impact on BUMDes financial reporting quality. Data were obtained through regulatory review, BUMDes financial statements, and quantitative simulation of biological asset growth/crisis scenarios. Analysis employed a comparative regulatory approach and financial impact simulation (Tables 1-4). The analysis reveals asset undervaluation, ROA distortion, extreme current ratios, and reduced information relevance due to the historical cost approach's failure to reflect biological asset value dynamics (biological transformation). This research enriches academic literature through specific comparative regulatory analysis between Kepmendesaa 136/2022 (SAK ETAP historical approach) and PSAK 241 (fair value approach) for BUMDes biological assets, implying the need for BUMDes accounting regulation adjustment by adopting PSAK 241 to align with the economic substance of biological assets. Keywords: Biological assets; Kepmendesaa 136/2022; PSAK 241; historical cost approach;